The influence of training intensity in the madrasah reform program on improving teacher competence - Afiandani, Mifta Lidya; Tolchah, Moch.; Zakariya, Din M. (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
The strategic plan of the Ministry of Religious Affairs to improve the quality of Islamic education in Indonesia includes the Madrasah Reform Program, designed to provide training relevant to the challenges of modern education. Teacher competence is a key factor in enhancing the quality of education. This study aims to analyze the influence of training intensity in the Madrasah Reform Program on improving teacher competence. A quantitative approach with an ex post facto method is used to evaluate the extent of the relationship between training intensity, which includes frequency, duration, and depth of material, and the improvement of teacher competence. Data were collected through questionnaires and documentation from madrasah teachers who participated in the training. The results of a simple linear regression analysis show that the depth of material has a significant impact on improving teacher competence. At the same time, the frequency and duration of training do not demonstrate a significant influence. These findings highlight the importance of the quality of training materials as a primary element in continuous professional development programs. Therefore, it is recommended that training focuses on preparing in-depth and applicable materials to enhance teacher competence effectively.